Opportunities to acquire foundational number sense: A quantitative comparison of popular English and Swedish textbooks - Löwenhielm, A; Marschall, G; Sayers, J; Andrews, P (European Society for Research in Mathematics Education, 2017)
In this paper, we present analyses of popular grade one textbooks, one from each of England and Sweden. Focused on Foundational Number Sense, we examine how each book’s tasks facilitate children’s learning of those number-related competences that require instruction and which underpin later mathematical learning. Analyses identified both similarities and differences. Similarities lay in books’ extensive opportunities for children to recognise and write numbers and undertake simple arithmetical operations. However, neither offered more than a few tasks related to estimation or simple number patterns. Differences lay in the Swedish book’s greater emphases on different representations of number, quantity discrimination and relating numbers to quantity, highlighting conceptual emphases on number. The English book offers substantially more opportunity for students to count systematically, highlighting procedural emphases.